Workshop on Finite Element Method (FEM) for final year project student and supervisors / Noorsuhada Md Nor ... [et al.] - Md Nor, Noorsuhada; Mat Saliah, Soffian Noor; Md Hasan, Ahmad Syauqi; Jamaludin, Amril Hadri; Fauzi, Mohd Azrizal; Ruslan, Amir Khomeiny; Hashim, Khairul Afinawati (Unit Penerbitan FKAPP, 2022)
A workshop on Finite Element Method (FEM) was held virtually on Microsoft Teams from 9th to 23rd December 2022. The workshop was led by Noorsuhada Binti Md Nor and attended by 21 final year project students, supervisors and staff from UiTM Cawangan Pulau Pinang. The workshop was conducted in collaboration with expert speaker Dr. Angga Fajar Setiawan from Universitas Gadjah Mada. The first day of the workshop, 9th December 2022, focused on "ABAQUS for Analysis". The participants were given an introduction to FEM concepts and available tools in ABAQUS. However, due to the high cost of ABAQUS, the participants used The ABAQUS Learning Edition, which is available free of charge and supports structural models up to 1000 nodes on Windows platform only. The subsequent days of the workshop, held on 12th, 16th, 19th, and 23rd December 2022, focused on "Elastic Modelling of Concrete Structures using Contact Interaction", "Inelastic Modelling of Concrete Structures containing Single Reinforcement", "Inelastic Modelling of Beams containing Doubly Reinforced Steel", and "Analysis of Simulation Results using Abaqus", respectively.